Analisis Kinerja Penanganan Stunting di Provinsi Sulawesi Barat Dengan Menggunakan Metode Logical Framework Analysis (LFA) - Widya Lestari; Basri Bado; Citra Ayni Kamaruddin; Abd. Rahim; Sri Astuty (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Stunting remains a serious challenge in human development, as it adversely affects development performance and economic growth, particularly in West Sulawesi Province, which has recorded the highest stunting prevalence in Sulawesi over the past several years. This study aims to analyze the performance of stunting reduction efforts in West Sulawesi Province by examining the alignment between policy objectives, program implementation, and achieved outcomes. The research adopts a qualitative approach using the Logical Framework Analysis (LFA) method. The data utilized are secondary data derived from development planning documents, program implementation reports, and official publications from relevant government institutions. The findings indicate that the high prevalence of stunting is influenced by limited access to nutritious food, poor sanitation and inadequate access to safe drinking water, a high incidence of early marriage, and the suboptimal implementation of accelerated stunting reduction programs. Based on the LFA results, policy recommendations for addressing stunting in West Sulawesi Province include strengthening food security and promoting local food diversification; improving community-based drinking water supply and sanitation facilities; enhancing education and awareness programs to prevent early marriage alongside the provision of educational assistance; and improving the quality and effectiveness of both specific and sensitive interventions implemented in an integrated and convergent manner through cross-sectoral synergy at the national, regional, and village levels. Addressing stunting requires a multidimensional and collaborative approach that involves strong cross-sectoral coordination, sustained commitment from local governments, active community participation, and the efficient and well-targeted utilization of funding sources, supported by continuous monitoring and supervision.